Eco-oriented urban planning: Integrating sustainable technological component in suburban zone regulation for the largest cities - Nadymov Ivan; Fedotov Grigory (E3S Web of Conferences)
The research considers the potential of the technological component of urban planning regulation of the suburban zone of the largest city (it is a city with a population of more than 1 million people). The suburban zone is a special territory inextricably linked with the core city in the agglomeration settlement system. The purpose of the study is to develop the concept of technological urban planning regulation of the suburban zone of the largest city. The study uses a system approach and software solution to show an example of the implementation of the study provisions. To achieve the stated goal, the socio-cultural prerequisites and the necessary theoretical basis of the research are reviewed, the theoretical concept of the research is formulated, and the algorithm of building the system of urban planning regulation of the suburban zone and its development management is demonstrated. The findings of the study show that the current possibilities of technological urban planning regulation of the suburban zone of the largest city are revealed in the potential of the territorial development management system with the help of software data processing methods, and this corresponds to the current demand for the creation of strong digital urban planning platforms.